Transformasi Limbah Kulit Bawang Menjadi Pupuk Organik Cair: Pemberdayaan Siswa SMP N 3 Salimpaung dalam Pengelolaan Lingkungan Berbasis Edukasi - Roza Helmita; Fitri, Rama Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Nagari Salimpaung, located near Mount Marapi, is characterized by its cool and fertile environment, making it highly suitable for agriculture, particularly vegetable farming. However, agricultural and household activities in the region generate a significant amount of organic waste, including onion peels, which are often underutilized and contribute to environmental pollution. A viable solution to address this issue is converting the waste into liquid organic fertilizer (LOF) through a fermentation process. This community engagement activity was conducted by students of UIN Mahmud Yunus Batusangkar during their community service program (KKN) on November 5, 2024, at SMPN 3 Salimpaung. A Community-Based Research (CBR) approach was applied, involving the school community in every stage, from problem identification to evaluation. The activity consisted of three stages: (1) Planning, which included discussions with teachers and students to identify environmental issues and select suitable solutions; (2) Implementation, which involved educating participants on organic waste management, demonstrating the LOF production process, and facilitating hands-on practice by students; and (3) Evaluation, which encompassed monitoring the fermentation process and assessing the quality of the resulting fertilizer. The results indicated that the eighth-grade students successfully participated in the socialization and independently produced liquid organic fertilizer. The fertilizer showed potential for application in local agriculture and home gardening. This activity not only enhanced students’ understanding of organic waste management but also equipped them with practical skills for sustainable environmental practices. The program is expected to serve as a starting point for broader waste management initiatives in Nagari Salimpaung.